Computational Methods, Seismic Protection, Hybrid Testing and Resilience in Earthquake Engineering A Tribute to the Research Contributions of Prof. Andrei Reinhorn - Cimellaro, Gian Paolo; Nagarajaiah, Satish; Kunnath, Sashi K. (Geotechnical, Geological and Earthquake Engineering, 2015)
The book is a tribute to the research contribution of Professor Andrei Reinhorn in the field of earthquake engineering. It covers all the aspects connected to earthquake engineering starting from computational methods, hybrid testing and control, resilience and seismic protection which have been the main research topics in the field of earthquake engineering in the last 30 years. These were all investigated by Prof. Reinhorn throughout his career.The book provides the most recent advancements in these four different fields, including contributions coming from six different countries giving an international outlook to the topics.